Evaluasi dampak dan rekomendasi perbaikan kebijakan anti bullying di SMK Negeri 2 Yogyakarta - Al-hadi, M. Zafif Hilmi; Matthew P, Harold; Noversa, Rikha; Hastutiningsih, Arum Dwi (Journal of Smart Education and Learning, 2025)
This study aims to evaluate the impact of and provide recommendations for improving anti-bullying policies at SMK Negeri 2 Yogyakarta. Using a descriptive qualitative approach, data were collected through in-depth interviews with the school’s Guidance and Counseling Coordinator. The findings reveal that bullying at SMK Negeri 2 Yogyakarta exhibits a complex pattern—ranging from verbal abuse to potential physical violence—with a high prevalence in male-dominated vocational departments (accounting for 80% of the 2,500 students). The school has implemented a comprehensive response system that includes preventive measures, such as a character education handbook and needs assessments, as well as curative strategies involving a tiered response system from mediation to disciplinary action. The School's Team for the Prevention and Handling of Violence (TPPK) serves as the central coordinator, supported by collaborative efforts with PUSPAGA and BPRSR in addressing severe cases. Key challenges include entrenched seniority culture and group dynamics among students. Recommendations for improvement include strengthening legal and procedural frameworks, developing proactive programs through a Teacher Empowerment Program, and optimizing multi-stakeholder collaboration. This study contributes to the development of effective anti-bullying strategies within vocational education settings.